Interrelated Industries and the Rate of Technological Change - Strassmann, W. Paul (Review of Economic Studies, 1959)
Journal Article Interrelated Industries and the Rate of Technological Change Get access W. Paul Strassmann W. Paul Strassmann Michigan Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 1, October 1959, Pages 16–22, https://doi.org/10.2307/2296047 Published: 01 October 1959